Impact of an Educational Intervention on Care Burden among the Caregivers of Patients Undergoing Hemodialysis. - Darwin John, Brincy; Jacob, Susan (International Journal of Nursing Research, 2023)
Background: Chronic kidney disease (CKD) is a major disease burden, which is affecting the population across the globe, CKD patients depends on hemodialysis to sustain life. These patients are cared by an informal support system comprises spouse, father, mother, daughter, son, or any other caregiver who are related or not related to patient. Providing continuous care for such type of patients whose prognosis, an irreversible outcome is an overwhelming experience for caregivers due to physical and psychological distress, limitations to their personal and social activities, and impending financial burden. Objective: The objective of this study was to assess the burden among the caregivers of patients undergoing hemodialysis before and after the educational intervention. Methods: A quasi-experimental one-group pre- and post-test design was used. Sixty participants were selected through non-probability convenient sampling. Care burden was assessed through standardized tool (Zarit Care Burden Interview) with r-value of 0.98. Results: Statistical analysis shows that the pre-test mean score was 45.63 with standard deviation (SD) of 10.42, whereas post-test mean score was 27.13 with SD of 8.69. Wilcoxon signed-rank test; a non-parametric test was applied, and P-value was found to be < 0.001 at 95% of the confidence interval (P < 0.05). Therefore, the educational intervention on home care management was found to be effective in reducing the care burden among the caregivers of hemodialysis patients. Conclusion: Hence, educational intervention on home care management was an effective reinforcement strategy to reduce the care burden among the care providers of hemodialysis patients.